1994
DOI: 10.1111/j.1365-2125.1994.tb04255.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG profile of litoxetine after single and repeated administration in healthy volunteers.

Abstract: 1 Litoxetine is a selective serotonin reuptake inhibitor with antidepressant activity in animal models and in depressed patients. 2 This double-blind, cross-over, placebo-controlled study was carried out in 12 healthy young male volunteers. The aim was to assess the EEG profile of litoxetine in parallel with its pharmacokinetics after a single dose or multiple administrations for 4 days (6 doses) of two dosages (10 mg and 25 mg). Spectral analysis of four EEG leads (F4-T4, F3-T3, T4-02 and T3-01) was done up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Although statistical comparisons of the pharmacokinetic parameters between groups were not relevant due to the small number of young subjects, the values appear to be similar (see Table 4). These values correspond with data reported elsewhere [20]. There was also no age related effect in the tolerability profile of litoxetine.…”
Section: Adverse Eventssupporting
confidence: 91%
See 1 more Smart Citation
“…Although statistical comparisons of the pharmacokinetic parameters between groups were not relevant due to the small number of young subjects, the values appear to be similar (see Table 4). These values correspond with data reported elsewhere [20]. There was also no age related effect in the tolerability profile of litoxetine.…”
Section: Adverse Eventssupporting
confidence: 91%
“…From these results, it can be seen that the psychological effects of litoxetine were relatively small and that in all of the tests drug effects were weak. This may be due to the relatively small group size, however other evidence suggests that litoxetine possesses a similar profile to nonsedating antidepressants [20].…”
Section: Adverse Eventsmentioning
confidence: 92%
“…Power of alpha oscillations could provide insight into EIB alterations due to its functional role in cortical inhibition (Klimesch, Sauseng, & Hanslmayr, 2007). For example, decreases in relative alpha power, thought to reflect enhanced cortical excitability (Klimesch et al, 2007), have been observed in healthy male participants (n = 12) following 1 week of litoxetine administration, an SSRI under development (Patat et al, 1994), as well as in depressed patients following 1 week of escitalopram administration (Leuchter et al, 2017). Another exploratory study in healthy male participants (Knott, Howson, Perugini, Ravindran, & Young, 1999; n = 14/group) found that decreased serotonin synthesis via tryptophan depletion was associated with a trend toward increased relative alpha power.…”
Section: Introductionmentioning
confidence: 99%
“…Power of alpha oscillations could provide insight into EIB alterations due to its functional role in cortical inhibition (19). For example, decreases in relative alpha power, thought to reflect enhanced cortical excitability (19,20), have been observed in healthy male participants (n = 12) following one week of litoxetine administration, an SSRI under development (21), as well as in depressed patients following one week of escitalopram administration (22). Another exploratory study in healthy male participants (23) (n = 14/group) found that decreased serotonin synthesis via tryptophan depletion was associated with a trend towards increased relative alpha power.…”
Section: Introductionmentioning
confidence: 99%